Pott's puffy tumor on an exceptional clinical case: review of the literature - Sanogo, Harouna; Diarra, Kassim; Konate, Nfaly; Elmehdi Elansari, Mohamed Saydi Ag Med; Bagayogo, Drissa Kaloga; Coulibaly, Kalifa; Sidibe, Youssouf; Keita, Mohamed Amadou (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Pott's tumor or Pott's puffy tumor or osteomyelitis of the frontal bone is a rare clinical presentation. It usually occurs as a complication of trauma to the frontal region, frontal sinusitis or by blood-borne spread, the infection can also spread inwards leading to an intracranial abscess. This is a 04-month-old, 7 kg infant with left frontal swelling with ipsilateral orbital extension. This swelling had been evolving for approximately 1 month. The computed tomography showed a hypodensity of liquid in the left fronto-orbital subcutaneous topography with an intense annular parietal enhancement in the arterial and late stages. Treatment consisted of surgical drainage under general anesthesia. We made the incision via the left pterional approach and undermining up to the frontal bone. From the pus about 40 cc then we proceeded to the debridement of necrotic tissues and curettage of the frontal bone which was lysed in places. The germ found was Burkhoderia pseudomallei gram-negative bacillus sensitive to C3G. Pott's tumor is a rare complication most often from untreated or poorly treated frontal sinusitis. This lack of knowledge raises fears of an evolution towards intracranial complications that could be life-threatening for patients.